After the Flood. Mobility as an Adaptation Strategy in High Mountain Oases. The Case of Pasu in Gojal, Hunza Valley, Karakoram - Kreutzmann, Hermann (DIE ERDE – Journal of the Geographical Society of Berlin, 2012)
The high mountain environment of the Hunza Valley in the Karakoram is characterised by significant potential energy, extended glaciation and related events that tend to threaten habitations and settlements. The village oasis of Pasu is taken as a case in point to highlight adaptation and coping strategies over a longer period. The village lands of Pasu have been shrinking over time owing to glacier outburst floods in the upper valleys. The inhabitants of Pasu have developed a set of coping strategies that are linked to mobility. Shifting populations to newly created irrigated oases in previously barren lands, out-migration to urban areas within the Karakoram and to metropolises in downcountry Pakistan in search of employment and education, international migration to overseas destinations, and the broadening of income generation by reducing the importance of agriculture in favour of services and tourism are measures of adaptation that are embedded into the sociopolitical and economic framework conditions. The shrinking village lands of Pasu have posed tremendous challenges to the mountain farmers, who have developed their own responses.